Home run! : science projects with baseball and softball - Bonnet, Robert L. (Enslow Publishers, 2010)
Provides suggestions and directions for science projects that use elements of baseball and softball to present and explain a variety of concepts, such as transfer of energy, friction, statistics, and others.